Differential Urbanization in Turkey: 1955-2000 - Ayse Gedik (European Regional Science Association (ERSA), 2003)
The purpose of this paper is to test the differential urbanization theory for the Turkish case during the 50 years between 1955 and 2000. The analyses are carried out both in terms of population and net migration of urban centers. The theory is first tested for the country as a whole, and subsequently for each of her three major regions with differing development levels. The findings for Turkey, in general, are consistent with the theory of differential urbanization. She and all her regions are found to be at the "early medium city" stage (ie., the first phase of "polarization reversal"). The timing of the stages in her three regions was consistent with their respective level of development. The special characteristics of the Turkish case and their effects on her urban system are discussed. In the light of the Turkish data, revisions of the "Differential Urbanization" theory are proposed. It is hypothesized that with the addition of early urbanization phase (pre-concentration phase) in our analysis, the largest growth rates are observed in the small, large, medium, and again in the small cities. Thus, the process seems to be similar to the inverted-U shape (bell curve) in the Alonso theory.
Keywords: 330